PEMBERDAYAAN MASYARAKAT DESA TLANAKAN MELALUI OLAHAN IKAN MENUJU MASYARAKAT PRODUKTIF DAN MANDIRI - Aunul abid (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
Natural resources are very potential in determining the direction of movement of a village or a certain region. Natural resources, if managed properly, help the economic development of a country, especially for people who inhabit coastal areas. For the people of Tlanakan village, the fishing profession is one of the professions that is maintained and is a livelihood that provides considerable profits. So far, the people of Tlanakan village have used the fish caught to sell to the market in a fresh (unprocessed) state. The goal to be achieved in PKM community service activities is to increase community productivity and independence through processed fish into fish chips and various other processed products. The method used in this study uses a qualitative approach with a type of descriptive research, which is a research that reveals or clarifies a phenomenon or event that occurs in the present. The data collection technique uses observation and interviews with village communities.